The Oxford handbook of Calvin and Calvinism - Gordon, Bruce 1962-; Trueman, Carl R. 1967- (Oxford handbooks online, 2021)
John Calvin was a leader of the European Reformation of the sixteenth century and the influence of his thought remains crucial in our world. This collection explores the origins of Calvin's thought and the theological, historical, and cultural circumstances in which they have evolved from Geneva to our times